The Impact of Digitalization of Public Service Policies on the Effectiveness of Administrative Services in Makassar City - Abdul Halim; Sumardi Sumardi; Nasir Nasir; Kahar Gani; Nasiratunnisaa Mallappiang (Jurnal Pemerintahan dan Politik Lokal, 2026)
Digital transformation in public services has become a primary focus for various local governments in Indonesia in an effort to improve administrative effectiveness and public satisfaction. Makassar City, as one of the major cities in Indonesia, has implemented a policy of integrated public service digitalization through various online platforms. This study was conducted to measure the extent to which policy digitalization influences the effectiveness of administrative services, while also identifying factors supporting its success. The purpose of this study was to determine the effect of public service policy digitalization on the effectiveness of administrative services in Makassar City. The research approach used was quantitative with a survey design. Primary data were collected through questionnaires distributed to 120 respondents consisting of civil servants and members of the public who use digital services. Data analysis was conducted with the help of SPSS software using validity and reliability tests and simple linear regression to examine the relationship between variables. The results showed that public service policy digitalization had a positive and significant impact on the effectiveness of administrative services. The implementation of digital-based systems increased service speed, reduced administrative errors, and strengthened bureaucratic transparency. Digitalization also played a role in building public trust in public institutions through more efficient and accountable service mechanisms. The study's conclusion confirms that the success of policy digitalization is highly dependent on infrastructure readiness, apparatus competence, and public digital literacy. The novelty of this research lies in the affirmation of a direct relationship between digital policy and the effectiveness of public services in the context of Indonesian local government, providing an empirical basis for technology-based bureaucratic reform.